Google Trends terms reporting rhinitis and related topics differ in European countries. Issue 8 (13th March 2017) - Bousquet, J.; Agache, I.; Anto, J. M.; Bergmann, K. C.; Bachert, C.; Annesi‐Maesano, I.; Bousquet, P. J.; D'Amato, G.; Demoly, P.; De Vries, G.; Eller, E.; Fokkens, W.J.; et al.
Abstract: Google Trends (GT) searches trends of specific queries in Google and reflects the real‐life epidemiology of allergic rhinitis. We compared Google Trends terms related to allergy and rhinitis in all European Union countries, Norway and Switzerland from 1 January 2011 to 20 December 2016. The aim was to assess whether the same terms could be used to report the seasonal variations of allergic diseases. Using the Google Trend 5‐year graph, an annual and clear seasonality of queries was found in all countries apart from Cyprus, Estonia, Latvia, Lithuania and Malta. Different terms were found to demonstrate seasonality depending on the country ‐ namely 'hay fever', 'allergy' and 'pollen' – showing cultural differences. A single set of terms cannot be used across all European countries, but allergy seasonality can be compared across Europe providing the above three terms are used. Using longitudinal data in different countries and multiple terms, we identified an awareness‐related spike of searches (December 2016).